2017
DOI: 10.1016/j.tifs.2016.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Refrigerated warehouses as intelligent hubs to integrate renewable energy in industrial food refrigeration and to enhance power grid sustainability

Abstract: Refrigerated warehouses as intelligent hubs to integrate renewable energy in industrial food refrigeration and to enhance power grid sustainability,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 5 publications
(5 reference statements)
0
17
0
1
Order By: Relevance
“…The utilization of renewable energy is easily affected by external factors; the energy output and load demand cannot be matched, which tends to cause energy shortage at peak and waste at valley [20][21][22]. With the development of energy storage technology, energy can be transferred in a time series through the charge and discharge strategy of energy storage.…”
Section: Energy Storage Technologymentioning
confidence: 99%
“…The utilization of renewable energy is easily affected by external factors; the energy output and load demand cannot be matched, which tends to cause energy shortage at peak and waste at valley [20][21][22]. With the development of energy storage technology, energy can be transferred in a time series through the charge and discharge strategy of energy storage.…”
Section: Energy Storage Technologymentioning
confidence: 99%
“…Deploying ES alongside co-located demand centres and RETs allows the power provided by the RET facility to be used by the demand centre as required, reducing congestion on the electricity network and lowering energy bills. Several studies have identified the potential for various forms of ES co-location with demand centres and RET, including at refrigerated warehouses [95], at university campuses [96], and as already discussed at airports [74]. However, to date there has been little in the form of policy to promote this as a market for ES.…”
Section: Es With Co-located Demand Centres and Retmentioning
confidence: 99%
“…Paper [30] proposes to supply refrigerated warehouses by means of renewable energy sources coupled with cryogenic energy storage systems. Such storage systems use the RES surplus electricity to liquefy and store liquid air.…”
Section: Energy Storagementioning
confidence: 99%